A non-canonical Aux/IAA gene MsIAA32 regulates peltate glandular trichome development in spearmint - Reddy, Vaishnavi Amarr; Saju, Jolly Madathiparambil; Nadimuthu, Kumar; Sarojam, Rajani (Frontiers in Plant Science, 2024)
Phytohormone auxin controls various aspects of plant growth and development. The typical auxin signalling involves the degradation of canonical Aux/IAA proteins upon auxin perception releasing the auxin response factors (ARF) to activate auxin-regulated gene expression. Extensive research has been pursued in deciphering the role of canonical Aux/IAAs, however, the function of non-canonical Aux/IAA genes remains elusive. Here we identified a non-canonical Aux/IAA gene, MsIAA32 from spearmint (Mentha spicata), which lacks the TIR1-binding domain and shows its involvement in the development of peltate glandular trichomes (PGT), which are the sites for production and storage of commercially important essential oils. Using yeast two-hybrid studies, two canonical Aux/IAAs, MsIAA3, MsIAA4 and an ARF, MsARF3 were identified as the preferred binding partners of MsIAA32. Expression of a R2R3-MYB gene MsMYB36 and a cyclin gene MsCycB2-4 was altered in MsIAA32 suppressed plants indicating that these genes are possible downstream targets of MsIAA32 mediated signalling. Ectopic expression of MsIAA32 in Arabidopsis affected non-glandular trichome formation along with other auxin related developmental traits. Our findings establish the role of noncanonical Aux/IAA mediated auxin signalling in PGT development and reveal species-specific functionalization of Aux/IAAs.